Navigating uncertainty: The role of tax avoidance and leverage in shaping firm value - Fajriyah, Isna Lailatul; Hayunintyas, Darrin Octavia Siski; Firmansyah, Amrie (WIM Solusi Prima, 2024)
This study examines the effect of tax avoidance on firm value, with company leverage as a moderating variable, focusing on infrastructure companies during the Covid-19 pandemic. Using financial data from infrastructure companies listed on the Indonesian Stock Exchange from 2020 to 2022, this study employed a purposive sampling method to select 22 companies, resulting in 66 observations. The findings reveal that tax avoidance practices during the Covid-19 pandemic do not have a significant relationship with firm value. Additionally, company leverage does not moderate the relationship between tax avoidance and firm value. During economic uncertainty caused by the pandemic, investors prioritize investment risk, potential returns, and market stability over tax avoidance practices. This study is limited to a sample of infrastructure sector companies during the pandemic, which restricts the generalizability of the findings. Future research could expand the scope by including samples from other sectors to provide a broader perspective on the relationship between tax avoidance and firm value during periods of economic disruption. This study contributes to the Financial Services Authority (OJK) by supporting efforts to oversee corporate financial strategies, including tax avoidance practices. These findings can assist OJK in developing balanced regulations that ensure corporate accountability while maintaining economic stability during periods of uncertainty.